ROLE OF MATRIX METALLOPROTEINASES IN THE PATHOGENESIS OF INTERSTITIAL LUNG INJURY (Global Conference on Medical and Health Sciences, 2026)
Matrix metalloproteinases (MMPs) play an important role in extracellular matrix degradation, inflammatory response, and tissue remodeling in interstitial lung diseases. Dysregulation of MMP activity contributes to fibrosis progression and structural damage of lung tissue.
Keywords: Matrix metalloproteinases, interstitial pneumonia, pulmonary fibrosis, extracellular matrix, inflammation, biomarkers, tissue remodeling.